Predicting the Influence of the Machining Parameters on the Tool Tip Temperature - Chowdhury, S.; Islam, Mohammad Nazrul; Boswell, B. (Springer, 2015)
This research has indicated that, by using a computer model, a numerical method can be effective in predicting the tool tip temperature. This allows the effects of changes made to the machining parameters to be simulated. Temperatures through the tool tip can therefore be reduced by using the optimum cooling method for particular machining parameters.